The Self-Radicalization of White Men: "Fake News" and the Affective Networking of Paranoia. (23rd March 2018) - Johnson, Jessica
Abstract: This article examines how paranoia is affectively networked through digital technologies, political performances, and social media to radicalize white men. Using actor-network theory and affect theory, this paper analyzes how acts of domestic terrorism perpetrated by white men are triggered beyond rationales of self-interest through the circulation of paranoia as affective value. Specifically, this piece investigates connections between the online and offline violence spurred by #pizzagate and the Unite the Right rally in Charlottesville, Virginia, by tracing relationships between U.S. counterterrorism efforts, the online proliferation of fake news, accusations of fake news lodged by the state against the press, Facebook algorithms, and agentive bots. This analysis argues that, rather than an individual pathology or self-contained anomaly, paranoia is an ecology that is affectively networked by state and nonstate actors, materializing in processes of digital communication such that the radicalization of white men has violent physical and structural effects.